2017
DOI: 10.1093/gbe/evx154
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of Sex Chromosome Dosage Compensation in Animals: A Beautiful Theory, Undermined by Facts and Bedeviled by Details

Abstract: Many animals with genetic sex determination harbor heteromorphic sex chromosomes, where the heterogametic sex has half the gene dose of the homogametic sex. This imbalance, if reflected in the abundance of transcripts or proteins, has the potential to deleteriously disrupt interactions between X-linked and autosomal loci in the heterogametic sex. Classical theory predicts that molecular mechanisms will evolve to provide dosage compensation that recovers expression levels comparable to ancestral expression prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
218
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(228 citation statements)
references
References 141 publications
(284 reference statements)
10
218
0
Order By: Relevance
“…Heliconius males, expression of Z genes is reduced below autosomal levels, but this dosage compensation mechanism is imperfect, with males showing increased expression relative to females on Z chromosome genes (Walters et al, 2015). However, the apparent incomplete dosage compensation could be a consequence of an uneven distribution of sex-biased genes on sex chromosomes (Gu & Walters, 2017, Huylmans, Macon, & Vicoso, 2017. Regardless, when we compare rates of divergence and adaptation for genes with sex-biased expression, the expectations of fast-Z evolution are not clearly met.…”
Section: Discussionmentioning
confidence: 99%
“…Heliconius males, expression of Z genes is reduced below autosomal levels, but this dosage compensation mechanism is imperfect, with males showing increased expression relative to females on Z chromosome genes (Walters et al, 2015). However, the apparent incomplete dosage compensation could be a consequence of an uneven distribution of sex-biased genes on sex chromosomes (Gu & Walters, 2017, Huylmans, Macon, & Vicoso, 2017. Regardless, when we compare rates of divergence and adaptation for genes with sex-biased expression, the expectations of fast-Z evolution are not clearly met.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the rate of turnover of XY versus ZW chromosomes is predicted to differ in light of mutation load. First, the evolution of complete dosage compensation, a mechanism that compensates for the degeneration and loss of expression of the W and Y chromosomes (Gu & Walters, ; Mank, ), is thought to reduce the power of purifying selection to maintain gene activity on these chromosomes (Engelstädter, ; Wright et al, ). Dosage compensation mechanisms are more frequently observed on XY relative to ZW chromosomes in the species studied so far (Gu & Walters, ; Mullon et al, ; Tables –S3), potentially leading to faster rates of Y chromosome decay.…”
Section: Future Directions and Perspectivesmentioning
confidence: 99%
“…First, the evolution of complete dosage compensation, a mechanism that compensates for the degeneration and loss of expression of the W and Y chromosomes (Gu & Walters, ; Mank, ), is thought to reduce the power of purifying selection to maintain gene activity on these chromosomes (Engelstädter, ; Wright et al, ). Dosage compensation mechanisms are more frequently observed on XY relative to ZW chromosomes in the species studied so far (Gu & Walters, ; Mullon et al, ; Tables –S3), potentially leading to faster rates of Y chromosome decay. However, there have been several recent counter‐examples to this trend (Hale, McKinney, Thrower, & Nichols, ; Huylmans et al, ), and as more sex chromosomes are identified it will be possible to test whether there is indeed a consistent relationship between dosage compensation status and sex chromosome system.…”
Section: Future Directions and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…As Ohno noted [1], ‘The so-called sex-linked genes are nothing more than the original Mendelian genes which were there when the X or the Z was an ordinary chromosome’. These ‘ordinary’ genes are under strong developmental constraint to maintain expression levels between males and females through dosage compensation [reviewed in 2], leading to the remarkable conservation of X chromosome gene content across placental mammals [3], known as Ohno’s law [see also 4]. But sex-linked genes are often more than just ordinary genes.…”
Section: Constraint and Conflict In Sex Chromosome Evolutionmentioning
confidence: 99%